Carbon vacancy in C3N4 nanotube: Electronic structure, photocatalysis mechanism and highly enhanced activity - Li, Yuhan; Gu, Miaoli; Shi, Ting; Cui, Wen; Zhang, Xianming; Dong, Fan; Cheng, Jinshui; Fan, Jiajie; Lv, Kangle (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Tubular g-C3N4 with carbon vacancy was obtained by pyrolysis under N2 atmosphere.•Carbon vacancy facilitates the adsorption of NO and O2 on the surface of g-C3N4.•Carbon vacancy accelerates the separation and transfer of photo-generated carriers.•g-C3N4 with carbon vacancy exhibits improved visible photocatalytic NO oxidation. We demonstrated that carbon vacancy modified C3N4 nanotubes can be qualified for more efficient and selective oxidation of NO to NO3− under visible light illumination than the pristine counterpart. Tubular C3N4 with carbon vacancy was fabricated by facile pyrolysis of the hydrolyzed melamine-urea mixture under N2 gas. With the particular structural merits for tubular nanostructure and the introduction of suitable carbon vacancy density, richly available surface defect sites, and accelerated separation and transfer of photo-generated charge carriers, the as-prepared carbon vacancy modified C3N4 nanotubes exhibited an excellent photocatalytic NO oxidation performance. Based on ESR measurement and DFT calculation, the electronic structure of carbon vacancy was revealed. The surface carbon vacancy in C3N4 nanotubes can greatly facilitate the adsorption of NO and O2, therefore, leading to its superior photocatalytic selectivity in conversion of NO to NO3−. The present work provides new insights into the understanding of defective semiconductor photocatalysis.